A closer look at the agent advantage effect: An eye-tracking study on event role processing in pictures - Xu, Wenjia; Huff, Markus; Papenmeier, Frank (Visual cognition, 2024)
The agent advantage effect refers to observers responding faster to someone acting (the agent) than to the person or thing acted upon (the patient). An eye-tracking study investigated this effect in an ecologically valid context. Participants viewed images of two fish, one biting the other, and searched for the agent or the patient, pressing a corresponding button. Reaction times and eye movements were recorded. Participants responded faster when searching for the agent, replicating the agent advantage effect. Eye-tracking data showed that participants' last fixations were more likely on the patient fish during patient search, a bias not found in first fixations or during agent search. A strong correlation between last fixations and reaction times suggests that the agent advantage effect may partly arise from extra cognitive resources spent on identifying the patient. These findings support that additional attention is required when identifying the patient, contributing to the agent advantage effect.